The Influences of COVID-19 on Patients With Chronic Kidney Disease: A Multicenter Cross-Sectional Study - Jiang, Zheng; Liu, Jiang; Geng, Lei; Zhong, Zhengxia; Tan, Jiaxing; Wen, Dongmei; Zhou, Ling; Tang, Yi; Qin, Wei (Frontiers in Psychiatry, 2021)
Background: The outbreak of coronavirus disease 2019 (COVID-19) has attracted global attention. During the lockdown period of COVID-19, follow-up of many patients with chronic disease had been interrupted, which brought severe challenges to better management of their disease. This study aimed at exploring the change of illness, daily life, and psychological responses during the COVID-19 pandemic among chronic kidney disease (CKD) patients. Methods: A total of 612 patients were enrolled in this study; 282 patients were categorized into the CKD stage 1–2 group and 330 patients were categorized into the CKD stage 3–5 group. Among two groups, 168 (27.5%) and 177 (28.9%) patients were female with a median age of 42 and 45, respectively. The study was conducted by collecting the questionnaires in five nephrology centers. The questionnaire consisted of assessment of anxiety by using the Self-Rating Anxiety Scale and the influences of COVID-19, which included basic demographic data, the influences of COVID-19 on illness and daily life, as well as the patients' psychological responses during the epidemic. Results: A total of 612 patients were included and divided into two groups according to eGFR. Ninety-six patients (34%) in the CKD stage 1–2 group and 141 patients (42.7%) in the CKD stage 3–5 group had reduced their follow-up frequency (p = 0.031). More patients with CKD stages 1–2 consulted online (25.9%), p = 0.005. Besides, patients in the CKD stage 3–5 group tended to be more anxious about follow-up (p = 0.002), fearful of being infected with COVID-19 (p = 0.009), and more likely to feel symptoms getting worse (p = 0.006). The standard scores of SAS were 48.58 ± 7.082 and 51.19 ± 5.944 in the CKD stage 1–2 group and the CKD stage 3–5 group, respectively (p < 0.001). There were significant differences in the severity of anxiety (p = 0.004). Conclusion: COVID-19 had a greater impact on patients with CKD stages 3–5 than those with stages 1–2 in terms of illness, daily life, and psychological disorder. Patients with CKD stages 3–5 were more anxious during the COVID-19 pandemic.